PERILAKU CYBER BULLYING PADA REMAJA - Mahasri Shobabiya; Rafi Iqbal Maulana; Dimas Faturrahman Hanafi; Muhammad Faruq Abbad Rosidi (CV. ADIBA AISHA AMIRA, 2024)
Cyberbullying is a form of bullying that is very vulnerable to occurring in teenagers, which is now easier and more often done using electronic or digital tools. The aim of this research is to determine cyberbullying behavior with its impact and the factors that influence cyberbullying behavior in adolescents. The method used by researchers is the library research method, library study. The results of the research were carried out by analyzing journals related to cyberbullying in adolescents. Based on the results of the analysis, it is known that Cyberbullying is an action carried out by a person or group of people against another individual via text messages, images/photos or videos that tend to be degrading and harassing. Apart from that, cyberbullying can have a serious impact on an individual's mental development, one of the negative impacts being low self-confidence. Feeling lonely and isolated from the surrounding environment. On the other hand, there are also internal factors, including; Internal behavior is related to the personality characteristics of the perpetrator who lacks empathy. The external factors are caused by the rapid development of technology, as well as the increasingly easy way for technology to provide open social media for teenagers.